Strategies to Reduce Food Loss and Waste in Emerging Economies: An Interpretive Structural Modelling Approach - Afif, E.L.; Ardi, R. (The South African Journal of Industrial Engineering, 2025)
This study aimed to develop a nationwide strategic framework to reduce the volume of food loss and waste in the context of developing countries. The research used expert opinions to validate the strategy derived from the literature review, and the interpretive structural modelling method (ISM) to construct a strategy in a structural hierarchy. The “matrice d’impacts croises multiplication appliquee aun classement” (MICMAC) analysis then categorised strategy elements based on driving forces and dependencies. Twenty recommendations for reducing food loss and waste (FLW) were organised in a structural strategy hierarchy. The hierarchy has seven levels, and most of the strategies are categorised as links in the MICMAC quadrant. Studies rarely find a structural hierarchy for a strategy using ISM, especially for food loss and waste reduction strategies.